CALCULATION OF OF RETAINING WALLS OF SOIL TYPE COUNTERFORT WITH GEOTEXTILE STRENGTHENING AT PROJECT MANAGEMENT LANDSLIDES ROAD SECTION VILLAGE MARGOMULYO KABUPATEN KUTAI KARTANEGARA - ANSYAH, SUDI (KURVA S JURNAL MAHASISWA, 2014)
Road infrastructure is one of the veins and supporting the economic development of society, particularly in rural areas. Good road infrastructure to support economic development and even can be a driver in driving development.Margomulyo village roads is the only access that connects the two regions with the Village District of Loa Janan Purwajaya, so that in the event of an avalanche on the road, it can cause Spontaneous isolated region. Landslide that occurred on roads in the form of sliding of the road that could potentially lead to these roads cut off, so we need a swift and appropriate action in dealing with avalanche that happened on these roads.From the calculation results can be concluded that, dimensional wall pehanan high ground is 3 meters and a width of 1 meter, 1 meter thick plate with a length of 10 meters per segment review, construction reinforced with geoteksil. Secure the stability of a retaining wall to bolster however affect the shear, so that the necessary foundation piles with additional bracing to the pile group to rigidify the structure of the walls and the pile.